The relationship between social participation and cognitive function early after surgery of glioma patients - Yinglian Xiao; Jing Tan; Guo Cheng; Yanhong Deng (PLoS ONE, 2025)
Objective Social Participation (SP) is known to benefit cognitive function. However, whether this positive relationship holds across the people with glioma has not been studied. The present study aimed to investigate the current status of SP and cognitive function of patients early after surgery with glioma, and therefore, explore the associations between cognitive function and SP. Methods This study included 179 postoperative patients with gliomas within 6 months of surgery. Cognitive functioning was measured by the Montreal Cognitive Assessment (MoCA) including orientation, attention, learning and memory, executive functioning and verbal fluency. Social participation was obtained also by questionnaire survey with the Impact on Participation and Autonomy Questionnaire (IPA). The Pearson correlation analysis was used to explore the relation between cognitive functioning and social participation, and the efficacy of social participation in predicting cognitive functioning was evaluated using the receiver operating characteristic (ROC). Results The prevalence of cognitive impairment in early postoperative glioma patients was 77.65%. The mean level of social participation was 37.96 ± 26.85 points, with poorer scores in the autonomy participation of family role and outdoor engagement dimensions. Patients’ cognitive functioning was positively correlated with social participation (r = −0.64, P < 0.001). And The areas under the ROC curve for social participation predicting cognitive function were 0.884. Conclusion Early post-operative cognitive impairment was more common in glioma patients, which was positively correlated with social participation. Social rehabilitation programs for glioma patients should be actively constructed to promote the social participation of patients early after surgery in order to protect their cognitive function.